ON THE ONSET TIME AND MECHANISM OF THE GREATER CAUCASUS UPLIFT AS WELL AS GENETIC TYPE AND FILLING HISTORY OF THE CISCAUCASIA TROUGHS – TRADITIONAL AND MODERN INTERPRETATIONS - N. B. Kuznetsov; T. V. Romanyuk (Геодинамика и тектонофизика, 2025)
The synthesis and analysis of new geological and geophysical data through the Black Sea-BalkanAnatolian-Caspian megaregion been appeared during the last two decades have been carried out. All collected materials make it possible to give a completely different interpretation of long-known facts and to provide a new-level consideration of the onset time and mechanism of the Greater Caucasus uplift, as well as genetic type and filling mechanism of the Ciscaucasia troughs. It has shown that the Greater Caucasus  orogen became a high and an intensively eroded mountain structure not earlier than the Pliocene. Its formation was not due to the Oligocene (or earlier) initiation of long-term tectonic near-meridional crustal shortening and slow gradual uplift, but occurred as a rapid uplift of the crustal block in the Pliocene – Quaternary in response to the delamination of a fragment of the lithosphere beneath the central part of the Caucasus region. The modern geomorphological appearance of the Greater Caucasus orogen was greatly contributed to by the deformations originated from large-amplitude right-lateral strike-slip movements with additional transpression along the regional Crimea-Caucasus-Kopetdagh fault zone, as well as from the gravitational collapse of the orogen. Most of the Cenozoic sediments, filling the Ciscaucasia troughs, have accumulated in the basin located in the northeastern part of the Eastern Paratethys. Until the Pliocene this basin was a pericratonic sedimentary basin on the southern shelf of Northern Eurasia, which experienced the accumulation of sediment transported primarily from the ancient East European and young epi-Hercynian Scythian platforms. The sedimentary basin, with relics as the Ciscaucasia troughs in the present-day structure of Ciscaucasia, was separated from the Eastern Paratethys by the rapidly uplifting Greater Caucasus orogen at the very end of the Pliocene – Quaternary and transformed into a piedmont trough wherein the sediment from the GC started to accumulate.